MATH 100, HOMEWORK 2 SOLUTIONS Section 2.7, #22: g(x) − g(0) 1 − x3 − 1 −x3 = lim = lim = lim (−x2 ) = 0. x→0 x→0 x→0 x x→0 x−0 x g 0 (0) = lim We also have g(0) = 1. Therefore the equation of the tangent is y = 1 + 0 · x, i.e. y = 1. Section 2.8, #26: 1 3 + x + h 3+x − h→0 h 1 − 3x − 3h 1 − 3x 1 (3 + x + h)(1 − 3x) − (3 + x)(1 − 3x − 3h) = lim h→0 h (1 − 3x − 3h)(1 − 3x) f 0 (x) = lim 1 (3 + x + h − 9x − 3x2 − 3xh) − (3 + x − 9x − 3x2 − 9h − 3xh) h→0 h (1 − 3x − 3h)(1 − 3x) = lim 1 10h h→0 h (1 − 3x − 3h)(1 − 3x) = lim = lim h→0 10 10 = . (1 − 3x − 3h)(1 − 3x) (1 − 3x)2 The domain of both f and f 0 is the set of all x where 1 − 3x 6= 0, ie. (−∞, 1/3) ∪ (1/3, ∞). Section 2.8, #28: √ √ 1 1 1 1 t− t+h √ √√ g (t) = lim − √ = lim h→0 h h→0 h t t+h t t+h √ √ √ √ 1 ( t − t + h)( t + t + h) √ √√ √ = lim h→0 h t t + h( t + t + h) 0 t−t−h √ √ = lim √ √ h→0 h t t + h( t + t + h) −1 −1 1 √ √ = − t−3/2 . √ = = lim √ √ h→0 2 t·2 t t t + h( t + t + h) 1 The domain of both g and g 0 is the set of all t 6= 0, ie. (−∞, 0) ∪ (0, ∞). Section 3.1, #30: v= √ 1 2 x+ √ = (x1/2 + x−1/3 )2 = x + 2x1/6 + x−2/3 , 3 x dv 1 2 1 2 = 1 + 2 · x−5/6 − x−5/3 = 1 + x−5/6 − x−5/3 . dx 6 3 3 3 Section 3.1, #54: The line y = 1 + 3x has slope we are looking √ 03, hence 0 3/2 0 for tangent lines with slope 3. We have y = (x x) = (x ) = 23 x1/2 . We first find all x where y 0 = 3: 3 1/2 x = 2, x1/2 = 2, x = 4. 2 At x = 4, y = 4 · 2 = 8. The tangent line that we are looking for has slope 3 and goes through the point (4, 8), therefore it has the equation y = 8 + 3(x − 4), or equivalently y = 3x − 4. 2